A Case of Melanoma-Associated Retinopathy, Uveitis, and Optic Neuritis Associated With Pembrolizumab, Managed With Topical, Intravitreal, and Intravenous Steroids. (June 2020) - Xie, Kate; Kong, Christina; Mehta, Mitul C.
Purpose: We report a case of advanced metastatic cutaneous melanoma with melanoma-associated retinopathy and pembrolizumab-related panuveitis and optic neuritis. Methods: The patient's condition was managed by systemic, topical, and intravitreal corticosteroids without discontinuing pembrolizumab. Results: After initiation of systemic and topical steroid treatment, optic nerve edema improved. He developed chronic uveitis with cystoid macular edema with improvement in symptoms with intravitreal dexamethasone implants. The patient demonstrated a decrease in all metastatic lesions and improvement in melanoma-associated retinopathy. Conclusions: The new checkpoint inhibitor class including pembrolizumab shows promise as a therapy for advanced metastatic melanoma in patients resistant to all other forms of chemotherapy. In general, immune-related adverse effects are responsive to steroid therapy. The trend for treatment of posterior uveitis due to pembrolizumab is to discontinue pembrolizumab. Our case suggests that even severe cases of uveitis may be sufficiently ameliorated by concurrent systemic, intravitreal, and topical therapy to allow continuation of treatment.